A history of three cities. Times of occupation in Madrid, Amsterdam, and Paris (1936-1945) - Pérez-Olivares, Alejandro (Hispania Nova, 2021)
This article offers a reinterpretation of the occupations that defined the “total war” historical context from the perspective of urban history and by putting into comparison three different cities: Madrid, Amsterdam, and Paris. In order to do this, it considers the influence of several realities typically associated to the urban world such as anonymity, mobility, the delicate distribution of resources or the cities scale itself in the maintenance of the order initiated by occupation regimes in 1939, 1940, 1944, and 1945. The text is organized around three case studies: the type of administration during the occupation, civil or military; the collaboration of the population with the authorities and the construction of post-conflict order based on the ruptures and continuities that defined the occupied cities.
Keywords: occupations; urban history; total war; public order; spatial turn